Application of Graph Colouring Algorithm in Course Scheduling Process - Borotan, Nella Lestari; Yuspita, Yulifda Elin; Annas, Firdaus; Darmawati, Gusnita (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Scheduling is a crucial aspect in every occurrence, ensuring that all processes are orderly. Gema Nusantara Bukittinggi Health Vocational School currently utilizes Microsoft Excel for managing subject scheduling, which often leads to scheduling conflicts. The objective of this research is to develop a web-based subject scheduling system for Gema Nusantara Bukittinggi Health Vocational School. The outcome of this research is a web-based subject scheduling system that is valid, practical, and effective, thereby serving as a useful tool for subject scheduling. This research is classified as research and development (R&D). The system development follows an incremental model with four stages: analysis, design, coding, and testing. The product was evaluated through three types of tests: validity, practicality, and effectiveness. The validity test, conducted with three experts, yielded a value of 0.80, indicating validity. The practicality test, carried out with three practitioners, resulted in a value of 0.97, signifying high practicality. The effectiveness test, involving fifteen teachers, achieved a value of 0.95, demonstrating high effectiveness. Based on the product testing results, it can be concluded that the research product, which is a web-based scheduling system, is suitable for use in the subject scheduling process at Gema Nusantara Bukittinggi Health Vocational School